2013
DOI: 10.1111/dsu.12185
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Facial Telangiectasias Using a Micropulse 1,064-nm Neodymium-Doped Yttrium Aluminum Garnet Laser

Abstract: The micropulse 1,064-nm Nd:YAG successfully treated facial telangiectasias with a high degree of patient satisfaction, minimal discomfort, and no adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 10 publications
0
28
0
Order By: Relevance
“…In his study of 6 patients, Pham [28] concluded that the Nd:YAG 1,064-nm laser system coupled with dynamic precooling and postcooling thermal quenching was effective and safe in treating vascular lesions. In a recent study of 20 patients with facial telangiectasias treated by means of Nd:YAG laser, Rose and Goldberg [36] reported that the treatment was associated with minimal discomfort and no adverse events, like in the patient group that we treated.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In his study of 6 patients, Pham [28] concluded that the Nd:YAG 1,064-nm laser system coupled with dynamic precooling and postcooling thermal quenching was effective and safe in treating vascular lesions. In a recent study of 20 patients with facial telangiectasias treated by means of Nd:YAG laser, Rose and Goldberg [36] reported that the treatment was associated with minimal discomfort and no adverse events, like in the patient group that we treated.…”
Section: Discussionmentioning
confidence: 94%
“…Rose and Goldberg [36] evaluated the efficacy of the FD QSNd:YAG (diode-pumped frequency-doubled Q-switched neodymium:yttrium aluminium garnet) laser (532 nm) for the treatment of facial telangiectasias of 30 adults. After only one session with this laser type, telangiectasias either improved or totally cleared.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the assessment by an independent researcher, satisfac-tory clearance was achieved in 75% of patients and complete clearance was evident in as many as 10%, while no patient was reported as having no clearance at all, or worsening or experiencing adverse events. Therefore, the investigators concluded that micropulse 1064 nm Nd:YAG laser is both safe and effective for the treatment of facial telangiectasia [57] . As far as the treatment of telangiectasias of the lower extremities using Nd:YAG laser is concerned, a model has been suggested, in accordance with the best treatment outcome achieved using a range of moderate fluences (100-200 J/cm 2 ) and pulse durations between 10 and 100 ms, in order to reduce excess dermis heating and pain [58] .…”
Section: Telangiectasiasmentioning
confidence: 99%
“…It was not until 1997, with the addition of cooling and shorter pulse widths [6], that the Nd:YAG laser became a viable therapeutic option for treatment of cutaneous vascular lesions [7]. More recently, an Nd:YAG laser with a 650-μs pulse width has proven to be a viable option for facial treatments without the complications of prior longer-pulsed devices [8].…”
mentioning
confidence: 99%